Indonesian Coffee Culture and Heritage: Demystifying the Heritage Value of Coffee Shops inside Historical Buildings in Jakarta and Bandung - Oktafarel, Kevin Mochamad; Khouw, Mario; Augusta, Dinda Nadhila; Arifin, Ali; Ekomadyo, Agus Suharjono; Susanto, Vanessa (Local Wisdom Jurnal Ilmiah Kajian Kearifan Lokal, 2021)
Coffee culture has existed in Indonesia for ages and has a long history. Its existence is indicated by coffee shops in various regions and areas in Indonesia, e.g., in heritage buildings or areas. This research aims to analyze coffee culture in historical coffee shops and coffee shops built in heritage buildings, followed by finding the benefit and impact of heritage value on their coffee culture. This research was done on two coffee shops in Jakarta (Kopi Es Tak Kie and Starbucks Filateli) and another two in Bandung (Warung Kopi Purnama and Starbuck Asia Afrika). Observation, literature study, and in-depth interviews with visitors, employees, and employers were conducted to gather the required information and data. This research shows that heritage values increase the attractiveness and value of the coffee shops mentioned, even though their way of interpreting and upholding them is different. The family-owned coffee shops uphold their heritage values by highlighting the shops' history, while the chain coffee shops uphold theirs by taking advantage of the historical buildings or areas as the main component of their identities.Â DOI:Â https://doi.org/10.26905/lw.v13i1.5088